Le Régime Foncier Congolais : Du Contact Avec La Civilisation Occidentale à La Veuille de La Loi n°73- 021 du 20 Juillet 1973 Dite Foncière - Lonu, Marie-Bernard Dhedya; Gehrin, Markus; Cordonier, Marie-Claire; Moke, Michel Ilume; Wa Bassa, Salomon Mampeta (European Scientific Journal, ESJ, 2017)
This study focuses on the description of the Congolese land system after formal contact with Western civilization. The contact between the western and Congolese civilizations intervened with the explorations. Moreover, it would have been necessary to wait for the constitution of the Independent State of the Congo to be able to formally speak of a contact of the civilizations. Indeed, the contact between the explorer and the native is not significant at this time. Moreover, land management did not fit into the objectives of these adventurers. Land management has proven to be indispensable with the advent of colonization on Congolese territory. During colonization, land management took into account the rights of indigenous peoples by devoting several categories of land. Moreover, after its accession to international sovereignty through its Independence, the young Congolese state began a land reform by domanialising all the lands. This, however, was even described as expropriation.